1988
DOI: 10.2482/haigan.28.19
|View full text |Cite
|
Sign up to set email alerts
|

Effects of protein-bound polysaccharide preparation(PSK) in small cell carcinoma of the lung.

Abstract: A randomized controlled study was conducted to investigate the effects of PSK in the treatment of small cell carcinoma of the lung (SCC). A total of 109 cases were given standard chemotherapy consisting of 1mg Vincristine, 200-400mg Cyclophosphamide, and 2-4mg Mitomycin-C weekly for 4 to 8 weeks, with or without radiotherapy. To the group allocated to PSK, 3g/day of PSK was orally administered along with the above treatment. Of 93 eligible cases, 46 were PSK and 47 were control group. Response rates for PSK an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…PSK is classified as an antitumor agent in Japan and is used in gastric, 3,4 colorectal, 5-7 and small-cell lung cancer. 8 Various antitumor mechanisms of PSK, involving the activation of immunopotentiating cytokine production, 11 inhibition of immunosuppressive cytokine production, 12 activation of effector cells such as cytotoxic T-cells, 13 natural killer 14 and dendritic cells, 15 improvement of Th1/Th2 balance, 16 inhibition of angiogenesis, 17 cancer cell invasion, 18 induction of apoptosis to cancer cells, 19 and the induction of human leukocyte antigen (HLA)-antigen expression on cancer cells, 20 were reported.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…PSK is classified as an antitumor agent in Japan and is used in gastric, 3,4 colorectal, 5-7 and small-cell lung cancer. 8 Various antitumor mechanisms of PSK, involving the activation of immunopotentiating cytokine production, 11 inhibition of immunosuppressive cytokine production, 12 activation of effector cells such as cytotoxic T-cells, 13 natural killer 14 and dendritic cells, 15 improvement of Th1/Th2 balance, 16 inhibition of angiogenesis, 17 cancer cell invasion, 18 induction of apoptosis to cancer cells, 19 and the induction of human leukocyte antigen (HLA)-antigen expression on cancer cells, 20 were reported.…”
Section: Discussionmentioning
confidence: 97%
“…8 We previously conducted a comparative study of UFT and UFT plus PSK in colorectal cancer patients 75 years of age or younger and reported a tendency of improved prognosis in the PSK combined immunochemotherapy group. 5 In addition, Ohwada et al reported a significant improvement of disease-free survival in patients with stage II or III colorectal cancer treated with a combination of UFT and PSK.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, PSK is used in combination with chemotherapy as postoperative adjuvant therapy for gastric cancer and curatively resected colorectal cancer [4,5], and in combination with other therapies, including chemotherapy, for small cell lung cancer [6]. PSK has been reported to inhibit tumor growth and metastasis in vivo.…”
Section: Introductionmentioning
confidence: 99%
“…In Japan, PSK has been approved as a drug to be used in combination with postoperative adjuvant chemotherapy for gastric, 10,11 and colorectal cancers [12][13][14] and with chemotherapy for small-cell lung cancer. 15 Multiple mechanisms of action have been reported, including the activation of cytotoxic lymphocytes, 16 enhanced production of cytokines, 17 inhibition of cancer metastasis through the suppression of tumor-growth factor beta 1 (TGF-␤1), 18 and augmentation of apoptosis through the inhibition of nuclear factor kappa beta (NF-B). 19 .…”
Section: Introductionmentioning
confidence: 99%